Guided : the secret path to an illuminated life - Jackson, Laura Lynne (The Dial Press, 2025)
"According to Laura Lynne Jackson, to answer these questions is to live an "illuminated life." Jackson knows that her psychic gifts are not unique to her. She believes that everyone is capable of perceiving energy, identifying, and interpreting messages sent to us by the Other Side. In Guided, Jackson shows that our loved ones who have passed form our Teams of Light, and that they never stop sharing their wisdom with us. By embracing the connections they reveal, we are put on a path to our best life--a life that Jackson calls illuminated. An illuminated life is one characterized by connectedness and creativity. It is one of alignment with purpose. It is a life of peace and confidence. And it is a life every one of us can discover for ourselves, if only we are open to the guidance that is sent our way. In Guided, Jackson shares the unforgettable and moving experiences of regular people who have learned how to respond to the messages sent to them by their Teams of Light in order to discover their higher paths. Offering solace and comfort though times of grief, and chockfull of inspiring, motivating stories, Guided points the way toward an illuminated life for us all"-- Provided by publisher.